Respostas
respondido por:
1
f(x) = x² +5x +6
a) f(-1)
f(-1) = (-1)² +5.(-1) +6
f(-1) = 1 -5 +6
f(-1) = 2
b) f(0)
f(0) = 0² +5.0 +6
f(0) = 6
Espero ter ajudado, bons estudos.
a) f(-1)
f(-1) = (-1)² +5.(-1) +6
f(-1) = 1 -5 +6
f(-1) = 2
b) f(0)
f(0) = 0² +5.0 +6
f(0) = 6
Espero ter ajudado, bons estudos.
dan130:
vlw amigo tmj
respondido por:
1
Onde possui o X,você vai substituir por -1
-1² +5.(-1)+6
1-5+6
=2
-1² +5.(-1)+6
1-5+6
=2
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás